Religious Coping in Stressful Situations - Nouman, Hani (Archive for the psychology of religion, 2016)
Religious coping has been found to help people in stressful situations. It takes place within a specific cultural religious/context yet its measurement has not always been adapted to the context of the study population. The aim of this study was to develop an instrument to measure religious coping among religious Jews—a population that has received little research attention—and assess the associations of religious coping strategies with emotional adjustment. The study was based on quantitative data gathered from 332 religious Jewish women, who were coping with stress. The findings support the utilization of three religious coping strategies by the participants: Seeking the Support of God, Seeking the Support of Rabbis, and Seeking the Support of the Community, which were found to be directly correlated with better emotional adjustment. This instrument can assist in evaluating and understanding religious coping with stressful situations and in culturally adapting psychosocial interventions to promote emotional adjustment.